Remotely engaged—The role of job crafting in the change of employees' engagement after an abrupt transition to remote work - Birman, Noa Ariel; Katz-Navon, Tal; Vashdi, Dana; Hofstetter, Hila (Frontiers in Organizational Psychology, 2024)
Introduction Many employees perceived the move to remote work due to the COVID-19 pandemic as an abrupt organizational change. While research on work engagement has examined this construct in different contexts, it is unclear what may happen to work engagement in such an extreme context and over the course of time. In the current study, we examined the relationship between time and employees' work engagement after an abrupt change as well as the way job crafting interacts with this relationship. We hypothesized that a pre-transition high level of approach crafting strategies will have a negative effect, harming employees' ability to maintain their engagement over time, while a pre-transition high level of avoidance crafting strategies will actually have a mitigating effect, weakening the decrease in engagement. Materials We used a three-wave longitudinal study design, collecting data during the first 3 months of the pandemic. The sample included employees from different organizations across the U.S randomly recruited through Amazon Mechanical Turk. We utilized a multilevel repeated measures approach to analyze the data. Results Results supported our first hypothesis, demonstrating a negative relationship between time and engagement such that engagement declined over time. Our second hypothesis was partially supported, showing that the job crafting strategy of increasing challenging demands moderated the relationship between time and engagement, such that for employees that job craft by increasing their challenging demands, at the onset of the transition, the decrease in work engagement over time was more substantial. We did not find support for our hypothesis regarding the positive effect of avoidance crafting strategies on the decrease in work engagement. Discussion Our findings suggest that the tendency to job craft by pursuing more challenging demands at the onset of the pandemic, as an approach strategy of job crafting, gives employees an unnecessary added workload that requires the use of more resources. Over time, this extra load, depletes resource reservoirs and prohibits remaining engaged over time. In contrast, other types of approach crafting strategies seem to have no such harmful effect. Our findings highlight the importance of context, suggesting that under specifics conditions some job crafting strategies may be more energy draining than others.